Patient blood management to reduce surgical risk. Issue 11 (27th August 2015) - Clevenger, B.; Mallett, S. V.; Klein, A. A.; Richards, T.
Abstract Background Preoperative anaemia and perioperative blood transfusion are both identifiable and preventable surgical risks. Patient blood management is a multimodal approach to address this issue. It focuses on three pillars of care: the detection and treatment of preoperative anaemia; the reduction of perioperative blood loss; and harnessing and optimizing the patient‐specific physiological reserve of anaemia, including restrictive haemoglobin transfusion triggers. This article reviews why patient blood management is needed and strategies for its incorporation into surgical pathways. Methods Studies investigating the three pillars of patient blood management were identified using PubMed, focusing on recent evidence‐based guidance for perioperative management. Results Anaemia is common in surgical practice. Both anaemia and blood transfusion are independently associated with adverse outcomes. Functional iron deficiency (iron restriction due to increased levels of hepcidin) is the most common cause of preoperative anaemia, and should be treated with intravenous iron. Intraoperative blood loss can be reduced with antifibrinolytic drugs such as tranexamic acid, and cell salvage should be used. A restrictive transfusion practice should be the standard of care after surgery. Conclusion The significance of preoperative anaemia appears underappreciated, and its detection should lead to routine investigation and treatment before elective surgery. The risks of unnecessary blood transfusion are increasingly being recognized. Strategic adoption of patient blood management in surgical practice is recommended, and will reduce costs and improve outcomes in surgery.